Drivers of systemic risk: Do national and European perspectives differ?. (March 2019) - Buch, Claudia M.; Krause, Thomas; Tonzer, Lena
Highlights: In Europe, national and supranational supervisors conduct macroprudential policy. We study whether the assessment of systemic risk differs across regional levels. Our dataset consists of 80 euro-area listed banks and covers the years 2005–2013. Banks' systemic risk and its drivers are similar across different regional levels. However, for some banks, we find evidence for a cross-border externality. Abstract: With the establishment of the Banking Union, the European Central Bank has been granted the power to impose stricter regulations than the national regulator if systemic risks are not adequately addressed at the national level. We ask whether there is a cross-border externality in the sense that a bank's systemic risk differs when applying a national versus a European perspective. On average, banks' contribution to systemic risk is similar at the two regional levels, and so is the ranking of banks. Generally, larger banks and banks with a lower share of loans are more systemically important. The effects of these variables are qualitatively but not quantitatively similar at the national versus the European level.